2009
DOI: 10.1155/2009/542979
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Biological Studies of Organotin(IV) Derivatives with o‐ or p‐hydroxybenzoic Acids

Abstract: Organotin(IV) complexes with o- or p-hydroxybenzoic acids (o-H2BZA or p-H2BZA) of formulae [R2Sn(HL)2] (where H2L = o-H2BZA and R = Me- (1), n-Bu- (2)); [R3Sn(HL)] (where H2L = o-H2BZA and R = n-Bu- (3), Ph- (4) or H2L = p-H2BZA and R = n-Bu- (5), Ph- (6)) were synthesized by reacting a methanolic solution of di- and triorganotin(IV) compounds with an aqueous solution of the ligand (o-H2BZA or p-H2BZA) containing equimolar amounts of potassium hydroxide. The complexes were characterized by elemental analysis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 38 publications
1
37
0
8
Order By: Relevance
“…Lipoxygenase (LOX) is an enzyme that takes part in the metabolism of arachidonic acid to leukotrienes, whose metabolism products were associated with tumor proliferation as angiogenesis factors [89,90]. A study of series of organotins with O-or p-hydroxybenzoic acid were performed by Abdellah et al [91] Organotin compounds inhibited the peroxidation of linoleic acid by LOX and the proliferation of sarcoma cells. Triphenyl organotins were more active than other homologous complexes with p-hydroxybenzoic acids.…”
Section: Mechanistic Insight For the Mode Of Actionmentioning
confidence: 99%
“…Lipoxygenase (LOX) is an enzyme that takes part in the metabolism of arachidonic acid to leukotrienes, whose metabolism products were associated with tumor proliferation as angiogenesis factors [89,90]. A study of series of organotins with O-or p-hydroxybenzoic acid were performed by Abdellah et al [91] Organotin compounds inhibited the peroxidation of linoleic acid by LOX and the proliferation of sarcoma cells. Triphenyl organotins were more active than other homologous complexes with p-hydroxybenzoic acids.…”
Section: Mechanistic Insight For the Mode Of Actionmentioning
confidence: 99%
“…Upon coordination these vibrations have disappeared generating new bands in 1630-1590 cm À1 and 1492-1360 cm À1 regions, for complexes (1)- (6), corresponding to the COO asymmetric and symmetric vibrations. Information about Dn COO (n as -n s ) values has proved to be important in providing further details on the Sn-carboxyl bonding scheme [37][38][39]. We could not detect n s in the IR spectrum of the protonated ligand (HOBz).…”
Section: Chemistrymentioning
confidence: 75%
“…Interestingly, the organotinbiological activities are greatly influenced by their various molecular structures and most of them are generally very toxic even at very low concentrations (Pellerito et al, 2006). Previous studies by (Gielen et al, 2000;Abdellah et al, 2009) using organotin derivatives had shown a significant cytotoxicity and anticancer properties against various types of human cancerous cells in in vitro studies including HT-29 colon adenocarcinoma cells (Girasolo et al, 2010). All novel organotin (IV) derivatives, with the exception of dimethyltin (IV), showed significant cytotoxicity in HT-29 and was suggested to induce cell death via apoptosis (Girasolo et al, 2010).…”
Section: Ojbsmentioning
confidence: 99%